2013
DOI: 10.1111/bjh.12675
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral blood involvement in patients with follicular lymphoma: a rare disease manifestation associated with poor prognosis

Abstract: SummaryFollicular Lymphoma (FL) is the second most common non-Hodgkin lymphoma (NHL) subtype and its course is heterogeneous. At diagnosis, some patients with FL manifest a detectable leukaemic phase (FL-LP), but this feature has been seldom described and is poorly characterized. Among 499 patients diagnosed with FL in Lyon-Sud hospital, 37 (7Á4%) had characteristic FL-LP (by cytological blood smears and flow cytometric analysis). In addition, 91/1135 FL patients from the PRIMA study presented FL-LP at study e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 31 publications
2
20
0
Order By: Relevance
“…Leucocytosis at presentation appears to be associated with a poor prognosis; particularly, there is a correlation with the degree of leucocytosis with increased mortality and decreased disease-free survival. In addition, associated nodal involvement compared with a pure leukaemic phase contributes to a poorer prognosis 1 3 5. These findings are consistent with the poor outcome demonstrated in our patient, whose demise was just 1.5 months from diagnosis.…”
Section: Discussionsupporting
confidence: 90%
“…Leucocytosis at presentation appears to be associated with a poor prognosis; particularly, there is a correlation with the degree of leucocytosis with increased mortality and decreased disease-free survival. In addition, associated nodal involvement compared with a pure leukaemic phase contributes to a poorer prognosis 1 3 5. These findings are consistent with the poor outcome demonstrated in our patient, whose demise was just 1.5 months from diagnosis.…”
Section: Discussionsupporting
confidence: 90%
“…Sarkozy et al reported 7.4 % of their cases to have leukemic involvement and had shorter progression free and overall survival compared to a group of follicular lymphoma without a leukemic spill. More than 4×10 9 /L circulating lymphoma cells was found to have a bad prognosis 17. In the present study out of the four patients in leukemic phase one patient expired, the second one had an initial response to chemotherapy, and the other two were lost to follow up.…”
Section: Discussionmentioning
confidence: 45%
“…In a recent report from Japan, Kodaira and colleagues showed that a leukemic presentation, which accounted for 21% of the cases, portends a worse progression-free survival (PFS) in patients with FL treated with chemoimmunotherapy [22]. More recently, Sarkozy and colleagues identified a leukemic phase in 7% of patients with FL, which was associated with a shorter PFS, independent of the FL international prognostic index (FLIPI) score and beta-2-microglobulin levels [23]. Of note, both studies have been presented solely in abstract form.…”
Section: Discussionmentioning
confidence: 99%